Greens assessment of RP-UPLC method for estimating Triamcinolone Acetonide and its degraded products compared to Box-Behnken and Six Sigma designs - Hossam M. Nassef; Hoda A. Ahmed; Mohamed A. El-Atawy; Tahani Y. A. Alanazi; Mahmoud A. Mohamed (Green Chemistry Letters and Reviews)
A study on green analytical chemistry aims to develop eco-friendly alternatives to hazardous substances and minimize waste generation. The study thoroughly examined various tools to determine their greenness. A newly validated RP-UPLC method was then employed quantitatively to detect Triamcinolone Acetonide (TRA) in a creamy pharmaceutical formulation using UPLC BEH C18 (50 × 2.1 mm, 1.7μm) column for analysis, with a detection wavelength set at 240 nm. The Box-Behnken design was developed to efficiently determine the optimal chromatographic conditions while minimizing the required trials. The study effectively assessed the impact of three independent variables on various responses, including retention time, tailing factor, and theoretical plates. The variables examined ethanol ratio, pH levels, and flow rate were meticulously tested to optimize experimental conditions. The utilization of desirability and overlay plots, along with a mobile phase of ethanol and purified water in a volumetric ratio of 30:70 and pH adjustment to 5.0. Calibration curves were constructed to assess the linearity of TRA within the concentration range of 2.5-50 µg/mL, yielding correlation coefficients (r = 0.9999). The accuracy was validated through recovery studies with the acceptable range of 99.6-101.2%. The specificity of the method has been validated by conducting forced degradation studies per ICH guidelines.